1996
DOI: 10.1007/bf00114624
|View full text |Cite
|
Sign up to set email alerts
|

Volvariella-treated Eucalyptus sawdust stimulates wheat and onion growth

Abstract: Conversion of sawdust, a major waste generated by the timber industry, to an agricultural supplement was explored. Beds made with a mixture of Eucalyptus sawdust and soil reduced the chlorophyll content and the growth rate of wheat seedlings. However, following treatment with Volvariella volvaceae and urea, the sawdust in growth beds enhanced both the chlorophyll content and growth of wheat seedlings. Application of treated sawdust to soil increased the biomass of both bulb and foliage of onion. This represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
4

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
1
0
4
Order By: Relevance
“…Buswell et al (1996), han empleado cepas de Volvariella para la bioconversión de restos lignocelulósicos. Por su parte, Ramanurthy et al (1996), señalan que al agregar aserrín de Eucalyptus a un suelo para su acondicionamiento y luego cultivar distintos tipos de vegetales, determinaron un decremento en el contenido de clorofila y en el crecimiento de las plántulas ensayadas, pero al realizar el mismo experimento con aserrín pretrado con cepas de Volvariella volvacea (Bull. Ex Fr.)…”
Section: Resultados Y Discusionunclassified
“…Buswell et al (1996), han empleado cepas de Volvariella para la bioconversión de restos lignocelulósicos. Por su parte, Ramanurthy et al (1996), señalan que al agregar aserrín de Eucalyptus a un suelo para su acondicionamiento y luego cultivar distintos tipos de vegetales, determinaron un decremento en el contenido de clorofila y en el crecimiento de las plántulas ensayadas, pero al realizar el mismo experimento con aserrín pretrado con cepas de Volvariella volvacea (Bull. Ex Fr.)…”
Section: Resultados Y Discusionunclassified
“…A closer look at the soil texture revealed that it is not only the salt content, but organic carbon content in the soil and useful micro-flora totally dependent on carbon content was almost extinct from the soil, thereby substantially eroding its self-fertilization capacity (Ramamurthy et al, 1996). This problem was compounded further by indiscriminate and prolonged use of pesticides of increasing toxicity to control pests of increasing virulence, which has diminished useful micro-flora (N 2 -fixers, phosphate solubilizers, sulphur oxidizers, carbon composters, ecto-/endo-mycorrhizae etc.)…”
Section: Surface/flood Irrigationmentioning
confidence: 99%
“…Αντίθετα, οVerdonck (1988) βρήκε ότι η άμεση ενσωμάτωση οργανικών υλικών, όπως το πριονίδι ή ο φλοιός δένδρων, στις καλλιεργούμενες εκτάσεις προκάλεσε φυτοτοξικότητα, μακροχρόνια ακινητοποίηση του αζώτου και αλατότητα. Επίσης, οιRamamurthy et al (1996) αναφέρουν φυτοτοξικότητα στα καλλιεργούμενα φυτά μετά από χρήση κομπόστας, η οποία όμως μειώθηκε με προσθήκη ειδικών μυκήτων στο κομποστοποιήσιμο υλικό, διαδικασία που δεν χρειάστηκε να εφαρμοσθεί στην παρούσα εργασία και αποτελεί σημαντικό συγκριτικό πλεονέκτημα. Συγκεκριμένα, οιRamamurthy et al (1996) βρήκαν ότι η προσθήκη ουρίας και του μύκητα Volvariella volvaceae σε έδαφος με κομποστοποιημένα τεμαχίδια φλοιού (πριονίδια) του δένδρου Eucalyptus tereticornis προκάλεσε θετική επίδραση στη φυτρωτική ικανότητα, την περιεχόμενη χλωροφύλλη και το ρυθμό αύξησης των σποροφύτων σιταριού και κρεμμυδιού.…”
unclassified
“…Επίσης, οιRamamurthy et al (1996) αναφέρουν φυτοτοξικότητα στα καλλιεργούμενα φυτά μετά από χρήση κομπόστας, η οποία όμως μειώθηκε με προσθήκη ειδικών μυκήτων στο κομποστοποιήσιμο υλικό, διαδικασία που δεν χρειάστηκε να εφαρμοσθεί στην παρούσα εργασία και αποτελεί σημαντικό συγκριτικό πλεονέκτημα. Συγκεκριμένα, οιRamamurthy et al (1996) βρήκαν ότι η προσθήκη ουρίας και του μύκητα Volvariella volvaceae σε έδαφος με κομποστοποιημένα τεμαχίδια φλοιού (πριονίδια) του δένδρου Eucalyptus tereticornis προκάλεσε θετική επίδραση στη φυτρωτική ικανότητα, την περιεχόμενη χλωροφύλλη και το ρυθμό αύξησης των σποροφύτων σιταριού και κρεμμυδιού. Προηγούμενη έρευνα τωνBeauchemin et al (1992) επίσης έδειξε ότι η άμεση εφαρμογή στο έδαφος υλικών με υψηλή περιεκτικότητα λιγνίνης και κυτταρίνης δεν ενδείκνυται για τις καλλιέργειες, επειδή αυξάνει τη συγκέντρωση ορισμένων στοιχείων του εδάφους προξενώντας φυτοτοξικότητα και αναστολή της βλαστικής ικανότητας των σπερμάτων.…”
unclassified
See 1 more Smart Citation